Yargıtay Kararları Işığında Sigorta Acentelik Sözleşmesinin Sona Erme Sebepleri ve Mali Sonuçlarının Değerlendirilmesi - (:unkn) unknown (My University, 2020)
Bu çalışmada sigorta şirketinin sigortacılık faaliyetini, sigorta acentesinin aracılık hizmetinden yararlanmak suretiyle yürütmesini sağlayan acentelik sözleşmesinin sona erme sebepleri ve sona ermenin doğurduğu mali sonuçlar ele alın-maktadır. Ticari iş niteliğini haiz sigortacılık ve acentelik faaliyetleri 6102 sayılı Türk Ticaret Kanunu ve 5864 sayılı Sigortacılık Kanunu hükümleri çerçevesinde değerlendirilmektedir.Çalışmada, acentelik sözleşmesinin sona ermesi ve doğurduğu mali sonuçlara ilişkin olarak çok sayıda tezahür eden uyuşmazlık yargıya intikal ettiğinden Yargıtay’ın yakın tarihli güncel kararlarına özellikle yer verilerek uygulamada dikkat edilmesi gereken hususlar vurgulanmaktadır.

In this study, the termination grounds and arising financial consequences of the agency contract which provides the insurance company to execute its insurance operations within the agency’s service. These matters are evaluated within the frame of Turkish Code of Commerce no. 6102 and formed solely to their nature, the Code of Insurance no.5864 since the insurance company and the agency execute commercial businesses. Although the main subject of this study is assessed theoretically, since there are serious numbers of conflicts between the insurance companies and the agencies related to the termination grounds and the financial consequences from them and since these conflicts turned to cases within huge amounts leading to the courts in practice, up to date and current rulings of Supreme Court of Appeal are stated especially within the purpose of data evaluation by analyzing the practice and also helping to minimize the wrong doings so that the important issues in practice that should be aware of are emphasized.
Grounds for Termination of Insurance Agency Contract and Evaluation of Its Financial Consequences within the Light of the Supreme Court Decisions